TWIN TWIN TRANSFUSION SYNDROME - Hilwah Nora (Universitas Syiah Kuala, 2013)
Abstrak. Twin-twin transfusion syndrome (TTTS) adalah suatu komplikasi dari kehamilan multipel monokorion yang berisiko tinggi menyebabkan kematian fetal/neonatus, terutama pada janin usia belum mampu hidup dan bila janin berhasil hidup maka janin tersebut berisiko mengalami gangguan jantung, syaraf dan mental. Anastomosis pembuluh darah antar janin berperan penting pada patofisologi terjadinya TTTS. Darah ditransfusikan secara tidak seimbang antara satu janin (donor) dengan janin yang lain (resipien). Transfusi ini menyebabkan penurunan volume darah janin donor. Hal ini mengakibatkan pertumbuhan janin donor menjadi terhambat. Sedangkan janin resipien mendapat darah yang berlebihan sehingga bias mengakibatkan gagal jantung. Abstract. Twin-twin transfusion syndrome (TTTS) is one of the most serious complications of monochorionic multiple gestations. It is associated with a high risk of fetal/neonatal mortality, especially in previable gestations, and fetuses who survive are at risk of severe cardiac, neurologic, and developmental disorders. Placental intertwin vascular anastomoses play a key role in the pathophysiology of TTTS. Blood can be transfused disproportionately from one twin (the donor) to the other twin (the resipient). The transfusion cause the donor twin to have decreased blood volume. This in turn leads to slower than normal growth than its co-twin. The resipien twins become overloaded with blood. This excess blood puts a strain on this baby’s heart to the point that it may develop heart failure.